How to coach people with psychiatric disorders in sports <subtitle>Qualitative evaluation of the teaching aid for the training with individuals with psychiatric disorders</subtitle> - Rahel Lauber; Daniela Loosli; Nikolai Kiselev (Hogrefe AG, 2023)
Abstract: Introduction: A new Swiss teaching aid - "Sport without Borders: People with Psychiatric disorders" - was published at the end of 2020 and then evaluated six months later. The main question of the present qualitative evaluation was to what extent different aspects of the three macro levels - design, content, and applicability of the teaching material - are assessed as appropriate by the current trainers of the voluntary exercise and sports groups for people with psychiatric disorders. Methods: For this purpose, eight (N=8) semi-structured interviews (maximum variation sampling) were conducted in spring 2021 with the trainers of various sports groups for people with psychiatric disorders in Switzerland. The recorded interviews were subsequently transcribed and analysed with nVivo according to Thematic Analysis. Results: The interviewees rated the teaching material as very successful and necessary in all aspects (design, content, and applicability of the teaching material). Regarding applicability of the teaching material, the interviewees mentioned the potential for development and expansion of sports groups, and mentioned interesting possible applications and needs. Discussion & Conclusion: The results show that the current trainers of voluntary exercise and sports groups for people with psychiatric disorders are generally very satisfied with the teaching material. Compared to the existing literature in the context of physical activity and psychiatry, the current teaching material has significant language differences (e.g., avoiding lengthy and complicated sentences, minimum of academic terms) and is strongly oriented to the mass sports (lay)-coaches with none or low (para)-medical or academic background.